SISTEM IDENTIFIKASI WAYANG KULIT PURWA ( PANDAWA LIMA ) (Information Technology and Telematics, 2013)
Identification is the process of recognizing a form wayang of the wayang characters, so that we can obtain information such as the name of a character in identification. The continued development of technology, everyone is trying to find an easy way to think very practical and automatic, in that it recognizes the difficulty of wayang kulit figure that according to the ancient and outdated. The purpose of this research is to design and create software that can identify wayang kulit using template matching method that can facilitate the learning process of wayang kulit. Some image processing is used to assist in the introduction of, among others, grayscale, smoothing, binerisasi, segmentation, and pattern recognition. This identification system uses shadow puppets Delphi7 programming and Microsoft Access as the database From the analysis there are some constraints on the various types of wayang kulit, because every region has different characteristics and the engraving so that each character has hundreds or even thousands of kinds. So the introduction of the wayang should be specific areas where the puppet is made, the image scale pattern recognition process greatly affect the recognition process of the final result. For the next research puppets expected more recognizable, not just the pandawa lima and future expected more automated system, so no need to pre-processing process again.Keywords: Wayang Kulit, Identification, Template Matching, Image Processing.